Schistosomiasis of the appendix with special reference to infestation with S. haematobium - Rose, Alistair Westland (The University of Edinburgh, 1936)
(1) The literature of Bilharziasis of the appendix is reviewed, and shown to lack histopathological detail; it is pointed out that no reference is made to S. Haematobium infections. (2) A selective extract is given of accepted modern views on the helminthology, and the natural and experimental pathology of the colon in Schistosomiasis. (3) A detailed account is given of the pathological technique employed in the examination of a series of thirty five appendices removed at operation from adult natives of Nigeria, thirty of whom were found to be excreting S. Haematobium ova in the urine. Digestion of the tissues is proved to be the most accurate method of detecting and diagnosing the type of ova present. (4) In this series it is shown that twenty (57 %) of the specimens are found to harbour S. Haematobium ova, and that in four (20% of the infected or 11.4% of the total specimens) gross pathology is evident. (5) The pathological findings in sixteen cases in which ova, but no gross pathology. were demonstrated are contrasted in detail with fifteen cases in which no ova were found; the conclusion is reached that except for the presence of the ova on microscopic examination, it is impossible to discriminate between them, and that ova can be present in comparatively large numbers without prevoking tissue reaction. (6) The symptoms and pathological reports of four Bilharzial infected cases showing gross pathology are given in detail; it is shown that the latter is directly attributable to the Bilharzial infection, and that a specific type of tissue reaction is present. (7) The pathological process is described in detail, and theories advanced to explain the formation of the pseudo -tubercle, and the origin and function of the cells which go to form it. (8) It is shown that certain facts observed in this investigation are believed to be incompatible with modern theories, especially in regard to the manner in which the ova are deposited; an hypothesis is elaborated which appears to answer all the known facts. It is suggested that there is room for further experimental work on this subject. While admitting the probable importance of the number and concentration of ova and the site where they are deposited,(the serous coat having been shown to be unduly sensitive), as factors in determining the presence of macroscopic lesions, it is believed that toxin from the adult worm may also play a part in the production of typical pseudo -tuberculous reaction, together with the effect of irritation and a toxin produced by the ova; and that macroscopic lesions are probably the result of repeated deposits of ova at intervals. (9) It is believed that as a rule ova held up in the tissues seldom escape. (10) In a proportion of cases under certain conditions Bilharzial infection of the appendix is capable of causing a chronic type of appendicitis, but more often it probably forms part of a general infection of the colon giving rise to symptoms of mucoid diarrhoea.